The Urgency of Building Legal Awareness on Care of Children in the Family - Suud Sarim Karimullah (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2022)
This paper presents an understanding of the urgency of building legal awareness of child care in the family to provide a legal sense of the importance of sustainable child care amid social life by sticking to the applicable legal rules. This study used a juridical-normative approach by referring to various legal instruments that apply in Indonesia. Then, to add references in this study, other legal materials relevant to the object of study are systematically studied. Furthermore, the results of this study explained that the protection of children is the responsibility and obligation of all elements of the nation, not only for certain groups, which can be found in the explanation in Law No. 39 of 1999 concerning Human Rights, as explained in the provisions of Article 52 that every child has the right to protection by parents, family, society and the state. Children’s rights are human rights, so for their interests, children’s rights are recognized and protected by law even when they are in the womb.